An empirical study of credit risk management level and influencing factors of Chinese commercial banks - Zheng, Hanyuan (2024)
The banking sector in China is expanding along with the country's financial sector, and its stability has an impact on how well the global and domestic financial markets operate. Therefore, it is becoming more and more crucial to conduct research on the credit risk of commercial banks in China. Using the theoretical underpinnings of the KMV model and RAROC model, this study will statistically analyse the credit risk management level of China's 12 systemically important commercial banks from 2007 to 2022 and examine variations in it in the context of various economic downturns. The relationship between a number of significant bank-specific factors and the banks' level of credit risk is then examined using the panel data regression model. It has been discovered that China's state-owned commercial banks manage credit risk substantially better than other commercial banks, but this gap is steadily closing as China's financial sector and regulatory level expand. Even though not every economic downturn has an impact and Chinese state-owned commercial banks are much more immune to external shocks than other commercial banks, economic downturns have an influence on the credit risk level of commercial banks. The profitability, size, asset quality, and regulatory indicators of commercial banks are all highly connected with their credit risk level from the standpoint of bank-specific characteristics. Therefore, it is suggested in this paper that commercial banks can increase their capacity to withstand credit risk and keep up sound operations by boosting their profitability and asset quality, increasing their business scale to raise more capital for risk coverage, sharpening their accurate assessment of their own credit conditions, and strictly upholding regulatory standards.